The effect of competition on managers’ compensation : evidence from a quasi-natural experiment - Ferreira, Priscila (2014)
This paper studies the effect of competition on executive compensation. We estimate the effect of increased product market competition on the performance-pay sensitivity of CEOs, and contrast it with the effect for department managers and other workers in the corporation. We use a recent reform that simplified firm entry regulation in Portugal as a quasi-natural experiment. The empirical strategy exploits the staggered implementation of the reform across municipalities. Using linked employer-employee data for the universe of workers and firms, we show that increased product market competition, following the reform, decreased the sensitivity of pay to performance of CEOs, with no significant effects found for other managers or workers. These findings are consistent with existing theoretical results in a principal-agent framework that a fall in entry costs leads to weaker managerial incentives.